Incidence and patterns of surgical site infections in a teaching hospital in central India - B. Hedaoo, Jagdish; N. Rathod, Vinod; V. Paramne, Amit (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2019)
Background: Surgical site infections (SSI) are one of the most common infections among the health care-associated infections. However, there is a scarcity of data on SSI from India. The present study was aimed to determine the incidences of SSI and to evaluate the associated factors at a hospital in Nagpur, central India region. Methods: Surgical sites were considered to be infected according to the set of clinical criteria recommended by the CDC’s NNIS system. The wounds were classified using the wound contamination class system, proposed by the American Centers for Disease Control (CDC) for use in SSI surveillance-1999, into Clean, Clean contaminated, Contaminated and Dirty wounds. Results: Among 2083 cases, 314 (15.1%) were suspected to be clinically infected, among them 250 (12%) were confirmed to have SSI. Among 2083 cases, 1214 (58.3%) operations included clean wound category and 869 cases (41.7%) were clean contaminated. From clean wounds 58 cases (4.8%) were found to be SSI and in clean contaminated wounds 192 (22.09%) cases were found to be SSI. Among the clean wounds, 103 (8.5%) were infected; about 58 cases (56.3%) were culture positive and 45 (43.7%) were culture negative. From the clean contaminated wounds, 211 (24.3%), 192 (91%) and 19 (9%) were found to be infected, culture positive and culture negative respectively. The studies of surgeries suggested that among clean surgeries Mastectomy was most common (14%), whereas Pyelolithotomy (8%) was the most common among the clean-contaminated surgeries. The prevalence of SSI was highest in Radical cystectomies (66.6%) and the least with lipoma excisions (6.4%). Conclusion: The incidences of SSIs in postsurgical infections were low in addition to this only small numbers of cases were confirmed to be SSIs. Though the reported cases are higher than the countries with high income, a well-planned strategy is required to decrease the incidences of SSI for improving the quality of health care system in present hospital and similar centers elsewhere.